Relief by intracoronary glyceryl trinitrate of coronary artery spasm resistant to sublingual route of administration. - Bentivoglio, L G (1981)
Inappropriate percutaneous transluminal coronary angioplasty of the anterior descending artery was avoided in a 52-year-old woman when the intracoronary administration of glyceryl trinitrate immediately before the angioplasty disclosed the organic component of the supposedly fixed, critical (80%) stenosis to be less than 50% of the lumen diameter. The spastic component of the stenosis had not been unmasked by the sublingual administration of two 0.4 mg tablets of glyceryl trinitrate during diagnostic angiography two weeks earlier. Intracoronary glyceryl trinitrate is indicated when suspected coronary spasm persists after the sublingual administration of this drug in potential candidates for percutaneous transluminal coronary angioplasty or coronary bypass surgery.